Guest Teacher Assistant Model - Yuriananta, Renda; Prakoso, Hikmal Teguh Budi; Wahani, Pradela Maynafia; Mulyani, Sekar Ayu Lestari; Ardhiansyah, Ikhwan; Frisdianti, Ananda Sanjaya (Universitas Negeri Malang, 2024)
Cooperative learning is crucial in today’s educational environment because the focus has shifted from teacher-centered to student-centered learning. A student-centered approach allows learners to gain experiences that help them retain information for a longer period. One model that is based on cooperative learning is the Guest Teacher Assistant Model. This model was developed by combining the TAI and TS-TS models, with the goal of helping students better understand the material. The steps in the Guest Teacher Assistant Model include forming heterogeneous groups of four, teacher-led material guidance, and having high-achieving students (acting as teacher assistants) assist their group members in understanding the material. Then, students visit other groups, with one member staying behind to act as the host, and share information by exchanging ideas, discussing, and sharing insights. After that, students return to their original groups for further discussion, write a group report, receive group recognition, and end with reflection.